Compact Stars in the QCD Phase Diagram - Blaschke, David (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The book edition of the Universe Special Issue "Compact Stars in the QCD Phase Diagram" is devoted to the overarching aspects shared between heavy-ion collisions and compact star astrophysics in investigating the hadron-to-quark matter phase transition in the equation of state of strongly interacting matter in different regions of the phase diagram of QCD. It comprises 22 review and research articles that, together, will serve as a useful guide in educating both young and senior scientists in this emerging field that represents an intersection of the communities of strongly interacting matter theory, heavy-ion collision physics and compact star astrophysics.